THE VALIDITY OF BAWASLU'S LEGAL DECISIONS HANDLING ELECTION VIOLATIONS - Mushafi Mushafi (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
This study will discuss the validity of the Bawaslu's decision on election violations. Because, according to preliminary findings, with the issuance of Law No. 7 of 2017 the position of Bawaslu is stronger. In this Law, Bawaslu in handling election disputes can not only provide recommendations to the KPU but also provide or make decisions that must be implemented by the parties. This means that Bawaslu currently has broader authority in handling election cases such as administrative violations and other violations. Then how is the validity of the legal decision from the Bawaslu? The method used in this research is in the category of normative legal research with a statute approach and a conceptual approach.